Ejercicios PVI FEM
Ejercicios PVI FEM
Ejercicios PVI FEM
Ejercicios Resueltos
Problemas de Valor Inicial
y 00 + y 0 = y 2 + t2 y(1) = 0 y 0 (1) = 2 1 ≤ t ≤ 2
b) Esquema Euler
xi+1 = xi + h (−xi + yi2 + t2i )
con y0 = 0 , x0 = 2
yi+1 = yi + h xi
1
Calculo de los dos primeros valores: h = =⇒ h = 0.001
100
x1 = x0 + h (−x0 + y02 + t20 ) x1 = 2 + 0.01 (−2 + 1) x1 = 1.99
=⇒ =⇒
y1 = y0 + h x0 y1 = 0.01. 2 y1 = 0.02
x2 = x1 + h (−x1 + y12 + t21 ) x2 = 1.99 + 0.01 (−1.99 + 0.022 + 1.012 ) x2 = 1.980305
=⇒ =⇒
y2 = y1 + h x 1 y2 = 0.02 + 0.01.1.99 y2 = 0.0399
c) Esquema RK4
h
xi+1 = xi + 6 (k11 + 2 k12 + 2 k13 + k14 )
con y0 = 0 , x0 = 2
h
yi+1 = yi + (k21 + 2 k22 + 2 k23 + k24 )
6
Recordemos el esquema:
0 k11 = f (xi , yi , ti ) k21 = g(xi , yi , ti )
x = f (x, y, t)
k12 = f (xi + 0.5 k11 h, yi + 0.5 k11 h, ti + 0.5 h) k22 = g(xi + 0.5 k21 h, yi + 0.5 k21 h, ti + 0.5 h)
,
k13 = f (xi + 0.5 k12 h, yi + 0.5 k12 h, ti + 0.5 h) k23 = g(xi + 0.5 k22 h, yi + 0.5 k22 h, ti + 0.5 h)
y 0 = g(x, y, t)
k14 = f (xi + k13 h, yi + h, ti + h) k24 = g(xi + k23 h, yi + k23 h, ti + h)
g(x, y, t) = x
Paso 1:
k11 = −x0 + y02 + t20
k11 = −2 + 02 + 12
k12 = −(x0 + 0.5 k11 h) + (y0 + 0.5 k11 h)2 + (t0 + 0.5 h)2 k12 = −(2 + 0.5 k11 .0.01) + (0 + 0.5k11 0.01)2 + (1 + 0.5 .0.01)2
,
k13 = −(x0 + 0.5 k12 h) + (y0 + 0.5 k12 h)2 + (t0 + 0.5 h)2 k13 = −(2 + 0.5 k12 .0.01) + (0 + 0.5 k12 0.01)2 + (1 + 0.5 .0.01)2
= −(x0 + k13 h) + (y0 + k13 h)2 + (t0 + h)2
k14 k14 = −(2 + k13 0.01) + (0 + k13 0.01)2 + (1 + .0.01)2
k11 = −1
k11 = −1
k12 = −(2 + 0.5 (−1) .0.01) + (0 + 0.5 (−1) 0.01)2 + (1 + 0.5 .0.01)2 k12 = −0.98495
=⇒ =⇒
k13 = −(2 + 0.5 3.005 .0.01) + (0 + 0.5 3.005 0.01)2 + (1 + 0.5 .0.01)2 k13 = −0.98503
= −(2 + 0.01) + (0 + 0.01)2 + (1 + 3.0352 .0.01)2 = 3.072
k14 k14 = −0.98003
k21 = x0
k21 = 2
k22 = (x0 + 0.5 k21 h) k22 = 2.0100
=⇒
k23 = (x0 + 0.5 k22 h)
k23 = 2.0101
k24 = (x0 + k23 h) k24 = 2.0201
h 0.01
x1 = x0 + (k11 + 2 k12 + 2 k13 + k14 ) x1 = 2 + 6 (−1 − 2 .0.98495 − 2 0.98503 − 0.98003)
6
=⇒
h
0.01
y1 = y0 + (k21 + 2 k22 + 2 k23 + k24 ) y1 = 0 +
(2 + 2 .2.0100 + 2 .2.0101 + 2.0201)
6 6
x1 = 1.9901
y1 = 0.020100
Paso 2:
k11= −x1 + y12 + t21
k11 = −0.96960
k12= −(x1 + 0.5 k11 h) + (y1 + 0.5 k11 h)2 + (t1 + 0.5 h)2 k12 = −0.95502
,
k13
= −(x1 + 0.5 k12 h) + (y1 + 0.5 k12 h)2 + (t1 + 0.5 h)2 k13 = −0.95509
= −(x1 + k13 h) + (y1 + k13 h)2 + (t1 + h)2
k14 k14 = −0.95027
k21 = x1
k21 = 1.9803
k22 = (x1 + 0.5 k21 h) k22 = 2.0001
=⇒
k23 = (x1 + 0.5 k22 h)
k23 = 2.0001
k24 = (x1 + k23 h) k24 = 2.0101
h 0.01
x2 = x1 + (k11 + 2 k12 + 2 k13 + k14 ) x2 = 1.9901 + 6 (−0.96960 − 2 .0.95502 − 2 0.95509 − 0.95027)
6
=⇒
h
0.01
y2 = y1 + (k21 + 2 k22 + 2 k23 + k24 ) y2 = 0.020100 +
(1.9803 + 2 .2.0001 + 2 .2.0001 + 2.0101)
6 6
x2 = 1.9805
y2 = 0.040100